EARLY PRESENTATION OF BILATERAL MORGAGNI HERNIA IN AN INFANT. CASE REPORT (Iraqi Journal of Medical Sciences, 2016)
In this report, a rare case of bilateral Morgagni hernia is enlightened in a 7-month old infant weighing 6.5 kg, presented with shortness of breath and fever for 5 days duration. There was a history of the same attack at 2 and 5 months of age and treated as a chest infection. He was admitted to pediatrics emergency unit for investigations and treatment. Plain chest radiography revealed retrosternal bowel herniation and Barrium-enema revealed bilateral big Morgagni hernia .Reduction of herniated contents (transverse colon and omentum) done with repairing of bilateral big Morgagni hernia through transabdominal approach. This case is a very rare and interesting one, because of an early bilateral presentation, and the fact that it occurred in a male infant.